design of a guide offering with the use of certain learning strategies modern to detect the talented (8-10) years on the psychomotor - براهيمي, قدور; بن سي قدور , حبيب (Journal of Sport Science Technology and Physical Activities, 2017)
This study aims to identify the effect of the use of a guide offering with the use of certain learning strategies modern to detect the talented (8-10) years on the psychomotor We used the experimental method, the sample of the study included 90 pupils of primary school distribute on three groups of 30 students (15 male and 15 female), They have been chosen at random, we use certain tests (30 m, flexion of the trunk from a standing position, race zigzag 4 * 10, jumping in numbered circles, stand on one foot and twisting right and left 15' body), We found that: the learning guide offer with the use of certain learning strategies active (cooperative learning, learning with games), contributes to the detection of talented students (8-10) years on the psychomotor, and as a result of this we recommend: the need of the application of learning strategies to educate talented students in themselves and their learning on their own skills to develop their talents in various sports activities